Antarctica’s uncertain future: global sea-level rise from oceanic and atmospheric forcing, with a focus on atmospheric rivers - Zou, Xun; Ralph, F. Martin; Bromwich, David H.; Gille, Sarah T.; Gorodetskaya, Irina V.; Mazloff, Matthew R.; Lubin, Dan; Cerovečki, Ivana; Sun, Rui; Wille, Jonathan D.; Zhang, Zhenhai (Frontiers in Earth Science, 2026)
Antarctic land ice stores the majority of Earth’s freshwater and carries substantial uncertainties regarding its future contribution to global sea level rise. While ocean processes associated with basal melting currently dominate ice loss, atmospheric forcing could have an increasing future impact, especially with intensified extreme weather events. For instance, atmospheric rivers, which are key drivers of long-distance moisture transport, introduce significant uncertainties to Antarctica’s ice mass balance, as they are capable of causing both intense snowfall and surface melting. They also impact ocean stratification and mixed-layer depth through freshwater input, ultimately affecting air-sea exchange. Associated interactions among components of the Earth system—atmosphere, ocean, and glacier—are not fully captured by global climate models and observations. This paper assesses Antarctica’s future, highlighting uncertainties stemming from limited understanding of atmospheric and oceanic forcings such as atmospheric rivers, and their consequences for projecting sea-level rise-related hazards.